HUBUNGAN TINGKAT PENGETAHUAN DENGAN SELF EFFICACY VAKSINASI COVID-19 PADA MAHASISWA UNIVERSITAS YATSI MADANI - Rafa Saflyah; Zahrah Maulidia Septimar (Nusantara Hasana Journal, 2022)
The Covid-19 vaccine has the aim of creating immunity for the community so that they can live productive daily lives in the midst of the Covid-19 pandemic. Herd immunity can be formed when the range of immunity is high and evenly distributed throughout the region. From an economic point of view, vaccines are more effective than drugs. Objective to determine the relationship between the level of knowledge and self-efficacy of covid-19 vaccination in Yatsi Madani University students. The design in this study used a cross sectional approach. Samples were taken using the Slovin formula with a total of 278 respondents. The sampling technique in this study used probability sampling with a simple random sampling approach. This study uses univariate analysis and bivariate analysis using Chi Square testGood Knowledge Level category as many as 252 respondents (90.6%). High Self Efficacy category as many as 248 respondents (89.2%). There is a significant relationship between the level of knowledge and self-efficacy with a p-value of 0.001. It was found that there was a relationship between the level of knowledge and self-efficacy of covid-19 vaccination in Yatsi Madani University students.